2015
DOI: 10.1016/j.jmii.2013.07.007
|View full text |Cite
|
Sign up to set email alerts
|

A population-based analysis of children with pneumonia among intensive care units in Taiwan

Abstract: The number of cases of pneumonia that required ICU admission was greater among younger children than among older children. Factors associated with the higher case fatality rate included older age at presentation, the need for invasive procedures (e.g., ET/MV, CVC insertion, chest tube insertion/drainage, and ECMO), underlying comorbidities and complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Araya et al [19] found that significant comorbidities (malnutrition, HIV, congenital heart disease [CHD], asthma, and Down syndrome) were associated with mortality (OR, 4.9-6.2). A retrospective study of children in the ICU with pneumonia found that cerebral palsy, epilepsy, and CHD were associated with mortality (OR, 1.49-2.37), whereas asthma was protective (OR, 0.17; 95% CI, 0.09-0.31) [41]. In a multicenter retrospective study comparing children hospitalized with aspiration pneumonia versus CAP, Hirsch et al [42] found that children with aspiration pneumonia had longer hospital length of stay (LOS) and were more likely to receive ICU care.…”
Section: Comorbiditiesmentioning
confidence: 99%
“…Araya et al [19] found that significant comorbidities (malnutrition, HIV, congenital heart disease [CHD], asthma, and Down syndrome) were associated with mortality (OR, 4.9-6.2). A retrospective study of children in the ICU with pneumonia found that cerebral palsy, epilepsy, and CHD were associated with mortality (OR, 1.49-2.37), whereas asthma was protective (OR, 0.17; 95% CI, 0.09-0.31) [41]. In a multicenter retrospective study comparing children hospitalized with aspiration pneumonia versus CAP, Hirsch et al [42] found that children with aspiration pneumonia had longer hospital length of stay (LOS) and were more likely to receive ICU care.…”
Section: Comorbiditiesmentioning
confidence: 99%
“…This program covers more than 99.5% of residents in Taiwan, and children younger than 18 years of age account for approximately 23% of the whole population in Taiwan [ 26 ]. The NHIRD provides reliable data for population-based disease research [ 27 30 ]. These datasets contain aggregated secondary data without personal identification, including patient′s age, gender, admission date, discharge date, diagnosis, expenses, laboratory examination items, detail drug prescription codes and operational codes [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pneumonia has been widely recognized as a complication of seizures. A population-based study on children admitted in intensive care revealed a similar finding that epilepsy was a significant risk factor for pneumonia [ 40 ]. The major cause was the aspiration of secretions, when seizure hindered the airway protective reflexes.…”
Section: Discussionmentioning
confidence: 90%